A modified prebind engagement process reduces biomechanical loading on front row players during scrummaging: a cross-sectional study of 11 elite teams - Cazzola, D.; Preatoni, E.; Stokes, K. A.; England, M. E.; Trewartha, G. (British Journal of Sports Medicine, 2015)
Aim: Biomechanical studies of the rugby union scrum have typically been conducted using instrumented scrum machines, but a large-scale biomechanical analysis of live contested scrummaging is lacking. We investigated whether the biomechanical loading experienced by professional front row players during the engagement phase of live contested rugby scrums could be reduced using a modified engagement procedure. Methods: Eleven professional teams (22 forward packs) performed repeated scrum trials for each of the three engagement techniques, outdoors, on natural turf. The engagement processes were the 2011/2012 (referee calls crouch-touch-pause-engage), 2012/2013 (referee calls crouch-touch-set) and 2013/2014 (props prebind with the opposition prior to the `Set` command; PreBind) variants. Forces were estimated by pressure sensors on the shoulders of the front row players of one forward pack. Inertial Measurement Units were placed on an upper spine cervical landmark (C7) of the six front row players to record accelerations. Players` motion was captured by multiple video cameras from three viewing perspectives and analysed in transverse and sagittal planes of motion.Results The PreBind technique reduced biomechanical loading in comparison with the other engagement techniques, with engagement speed, peak forces and peak accelerations of upper spine landmarks reduced by approximately 20%. There were no significant differences between techniques in terms of body kinematics and average force during the sustained push phase. Conclusions: Using a scrum engagement process which involves binding with the opposition prior to the engagement reduces the stresses acting on players and therefore may represent a possible improvement for players` safety.